A concept study on community based disaster management system in Malaysia - Ajayi, Binyamin Adeniyi; Hussein, Bakhtiyar A; Naseer, Mustafa; Ahmad Dahlan, Abdul Rahman (University Sultan Zainal Abidin, 2011)
The current study explores the effort a nation; Malaysia, is putting in, using the knowledge and prowess enabled by the field of Information and Computer Technology, in managing disasters; both naturally and man-made; it feels strongly that the community; the institution of the mosque, in this case; through its coordinating agencies, could be incorporated into a collaborative systems with the government agencies on the management of such occurrences as they are seen to be the closest to the populace. This will no doubt, in our view, imply a change in attitude but it will indeed make the perpetual efforts of the Government agencies to yield the required results.We thus opined that training these communities, which is expected to institutionalize a comity of volunteers, in the science of how to gather information and make good use of same in the event of the disaster occurrence will go a long way in making the tax payer money worthwhile. This will invariably be a step towards the realization of a minimal after effect of such incidences when they inevitably occurred.